The comparison between the effect of biochar, compost and biochar-compost mixture on plant growth performance and nutrients uptake / Mohamad Zuhelmi Adli - Adli, Mohamad Zuhelmi (Faculty of Plantation and Agrotechnology, 2019)
A glasshouse study was conducted to investigate the effect of empty fruit bunch (EFB) biochar, EFB compost and EFB biochar-compost as the soil amendment in plant growth medium. The objective of this study was to identified the effect of soil properties and plant growth performance by using EFB biochar, EFB compost and EFB biochar-compost mixture on the plant growth. There were four treatments and three replications namely control (untreated soil), 10 ton/ha of EFB biochar, EFB compost-biochar and EFB composted. The quantities of biochar and compost was measured based on the bulk density of the soil. The results show that the treatment two with 10ton / ha EFB biochar is the best rate for plant growth performance as it is significant for the plant height, soil pH, and the total plant dried biomass. For plant height, treatment two increased 12% from treatment one to 168cm. for soil pH content, treatment two is increased by 3% from treatment one to 5.2pH. Meanwhile, for the amount of total plant dried biomass, treatment two also increased by 45% from treatment one to 150g. In addition, there are also different macronutrients in different treatment.